The dimension of islamic spirituality in handling suicidal ideation: a systematic literature review - Anisa Siti Nurjanah; Sindi Ayudia Pama; Boy Haryono (Asian Journal of Islamic Studies and Society, 2024)
Suicidal ideation is a global mental health problem that has serious impacts on individuals, families, and communities. In the context of Muslim societies, Islamic spirituality is believed to play a crucial role in the prevention and management of suicidal ideation. This article aims to systematically review the literature related to the role of Islamic spirituality in managing suicidal ideation. Methods systematic literature review. This study was conducted by reviewing articles published between 2014 and 2024 from the Scopus database. The results indicate that the dimension of Islamic spirituality plays a significant protective factor in the prevention and treatment of suicidal ideation. Islamic values such as tawakkul (religious trust), patience, and the meaning of life provide psychological strength, while Islamic counseling has proven effective when integrated with modern psychotherapy approaches. However, more robust empirical research and standardized interventions are needed to strengthen the evidence of its effectiveness.